UPAYA MENINGKATKAN PARTISIPASI BELAJAR SISWA MELALUI MODEL FLIPPED CLASSROOM BERBANTUAN MICROSOFT OFFICE SWAY - Abdul Hakim; Siswandari Siswandari; Nurhasan Hamidi (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2022)
ABSTRACT This research aimed to examine the increase in learning participation of students in grade XI of Accounting and Institutional Finances expertise programs in the creative products and entrepreneurship subject at one of the Surakarta Vocational High School through the application of the flipped classroom learning model assisted by Microsoft Office Sway. This research is classroom action research. This research took place in two cycles. Each cycle consists of four stages, namely; planning, action, observation, and reflection. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusion. Data collection techniques used are observation, interviews, questionnaires, and documentation. The data validity technique used in this study is source triangulation. Based on the action results, it can be seen that learning using the flipped classroom learning model assisted by Microsoft Office Sway can increase student learning participation in cycle I and cycle II. In the pre-action, the percentage of student learning participation was 50.46%. After using the flipped classroom learning model assisted by Microsoft Office Sway in the first cycle, student learning participation reached 60.76%. In the second cycle, student learning participation reached a percentage of 78.24%. Based on the data above, it can be concluded that the flipped classroom learning model assisted by Microsoft Office Sway can increase the learning participation of students of grade XI of the Accounting and Institutional Finance expertise program in the creative products and entrepreneurship subject.. Keywords: learning participation, flipped classroom, Microsoft Office Sway. ABSTRAK Penelitian ini bertujuan untuk mengkaji peningkatan partisipasi belajar siswa kelas XI program keahlian Akuntansi dan Keuangan Lembaga pada mata pelajaran produk kreatif dan kewirausahaan di salah satu Sekolah Menengah Kejuruan Surakarta melalui penerapan model pembelajaran flipped classroom berbantuan Microsoft Office Sway. Penelitian ini termasuk jenis penelitian tindakan kelas. Penelitian ini berlangsung dua siklus. Masing-masing siklus terdiri dari 4 tahap yaitu perencanaan, tindakan, observasi, dan refleksi. Teknik analisis data berupa pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Teknik pengumpulan data menggunakan observasi, wawancara, angket, dan dokumentasi. Teknik validitas data penelitian ini menggunakan triangulasi sumber. Berdasarkan hasil tindakan, dapat diketahui bahwa pembelajaran dengan menggunakan model flipped classroom berbantuan Microsoft Office Sway dapat meningkatkan partisipasi belajar siswa pada siklus I dan siklus II. Pada pratindakan persentase partisipasi belajar siswa 50,46%, setelah menggunakan model pembelajaran flipped classroom berbantuan Microsoft Office Sway pada siklus I, partisipasi belajar siswa mencapai 60,76%. Pada siklus II partisipasi belajar siswa mencapai persentase 78,24%. Berdasarkan data di atas dapat disimpulkan bahwa model pembelajaran flipped classroom berbantuan Microsoft Office Sway dapat meningkatkan partisipasi belajar siswa kelas XI program keahlian Akuntansi dan Keuangan Lembaga pada mata pelajaran produk kreatif dan kewirausahaan. Kata Kunci: partisipasi belajar, flipped classroom, Microsoft Office Sway